1998
DOI: 10.1088/0953-4075/31/18/009
|View full text |Cite
|
Sign up to set email alerts
|

Temporary anions - calculation of energy and lifetime by absorbing potentials: the resonance

Abstract: The calculation of energies and lifetimes of metastable molecules requires the treatment of both the continuum and correlation effects. We describe the complex absorbing potential approach incorporated within a configuration-interaction framework. The absorbing potential method allows a very efficient solution of the continuum problem, making possible a detailed study of the correlation effects that turn out to be surprisingly strong. The famous N − 2 2 g resonance is studied as a test case and much attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
133
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 44 publications
2
133
0
1
Order By: Relevance
“…, 9, and for the laserphoton basis, we included the simultaneous emission and absorption of up to 20 photons. The non-Hermitian Hamiltonian matrix (dimension 41000) was diagonalized using a Lanczos algorithm for complex-symmetric matrices [14]. All results are converged with respect to the electronic and photonic basis sets and the number of Lanczos iterations.…”
mentioning
confidence: 99%
“…, 9, and for the laserphoton basis, we included the simultaneous emission and absorption of up to 20 photons. The non-Hermitian Hamiltonian matrix (dimension 41000) was diagonalized using a Lanczos algorithm for complex-symmetric matrices [14]. All results are converged with respect to the electronic and photonic basis sets and the number of Lanczos iterations.…”
mentioning
confidence: 99%
“…Santra and Cederbaum [7] not only showed that such a process is energetically possible but also proved that it is very efficient. Utilizing the CAP-CI (configuration interaction with complex absorbing potential) technique [11] they calculated a decay lifetime of about 80 fs for the one-site inner-valence excited states of the (Ne 2 ) 2+ dication. As in the case of singly ionized clusters other related processes such as ETMD can occur as well.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed advances in ab initio quantum chemical techniques using the analytical continuation methods for probing the electronic resonances in atoms and molecules [1][2][3][4][5][6][7][8][9][10]. The advantage of analytical continuation of the Hamiltonian in the complex plane giving the direct access to the resonances parameters is that they can be represented by using L 2 wavefunction [1].…”
Section: Introductionmentioning
confidence: 99%
“…The electron correlation and relaxation effects are clearly crucial factors in the formation and decay of the metastable states [6,15]. The accuracy of the effective oneparticle based approximations in the case of an electron scattering resonance depends on the extent to which the electron correlation is important in the description of particular states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation